Internalization of Character Values through the Rokat Tase’ Tradition: A Systematic Literature Review in the Context of Coastal Education in Madura - Muhammad Romli; I Wayan Suastra; I Nengah Suastika; Ni Ketut Suarni; I Wayan Lasmawan; Ida Bagus Putu Arnyana (FKIP - Universitas Riau, 2026)
This study aims to analyze the character values contained in the Rokat Tase’ tradition and its relevance for strengthening character education in coastal communities of Madura. This research is based on the limited integration of local wisdom traditions into formal character education, particularly in coastal areas. The study employed a Systematic Literature Review (SLR) method using PRISMA guidelines by identifying, selecting, and analyzing seven relevant empirical studies published between 2019 and 2024. Data were analyzed thematically to identify dominant character values and their educational implications. The results show that the Rokat Tase’ tradition reflects important character values, including religiosity, social solidarity, responsibility, environmental awareness, and cultural identity. These values are developed through collective rituals, social interaction, environmental practices, and intergenerational cultural transmission. Furthermore, the identified values are consistent with the objectives of character education and the Pancasila Student Profile, especially for students living in coastal and maritime environments. In conclusion, the integration of Rokat Tase’ into learning activities can be effectively implemented through contextual learning approaches, project-based learning, experiential learning, and value clarification techniques, making character education more meaningful and culturally relevant.